Preparation method for improving coercivity and squareness of neodymium-iron-boron magnet
By performing aging heat treatment in an inert atmosphere, the problems of insufficient coercive force and narrow aging temperature zone in high temperature environments are solved, and the coercive force and squareness of the magnet are significantly improved.
Patent Information
- Application Number
- CN202510144988.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-10
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing neodymium iron boron magnets lack coercive force in high temperature environments, and the aging temperature range of low B and high Cu-Ga sintered magnets is narrow, and rare earth elements are severely volatile, resulting in low squareness and low coercive force of the magnet.
Aging heat treatment is carried out in an inert atmosphere, the rare earth saturated steam pressure in the furnace is adjusted, the formation of 6:13:1 grain boundary phase is promoted, and the coercive force and squareness of the magnet are improved.
It significantly improves the coercive force and squareness of the neodymium iron boron magnet, broadens the aging temperature zone, reduces the volatility of rare earth elements, and optimizes the microstructure of the magnet.
Smart Images

Figure CN119601369A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of NdFeB magnets, in particular to a preparation method for improving the coercive force and squareness of NdFeB magnets. Background Art
[0002] Sintered NdFeB permanent magnet materials are widely used in energy, information, transportation, medical and national defense fields due to their excellent magnetic properties. In recent years, in order to meet the "dual carbon" policy, the application of NdFeB permanent magnet materials in the field of clean energy has continued to rise, prompting the rapid development of my country's NdFeB industry, and the prices of medium and heavy rare earth elements have risen due to excessive consumption. In particular, the prices of heavy rare earth elements Tb and Dy, which have low reserves, have continued to rise to 5 to 20 times that of Nd and Pr. Therefore, the development of heavy rare earth-free sintered NdFeB materials is not only an urgent need for the sustainable development of the NdFeB industry, but also a strategic need for the balanced development and efficient utilization of my country's rare earth resources.
[0003] High-temperature demagnetization is one of the key problems of NdFeB magnets, which restricts their application in high-temperature environments. If NdFeB magnets are to be used at high temperatures, their coercivity at room temperature needs to be improved. The strong magnetism of NdFeB magnets comes from the intrinsic magnetism of its 2:14:1 main phase. Its coercivity and temperature stability can be improved by substitution with heavy rare earths such as Tb / Dy. However, heavy rare earth substitution leads to a decrease in remanence and is expensive. Therefore, from the perspective of industrial development, improving the room temperature coercivity of magnets without adding heavy rare earths is an important research direction in the field of rare earth permanent magnets.
[0004] In the early stage, the grains were refined by combining helium gas jet milling and pressureless sintering process, so that the coercivity of the heavy rare earth-free magnet was increased to 20 kOe. However, the 1-micron magnetic powder obtained by this method is very easy to oxidize, and the equipment requirements are very high. Due to equipment limitations, it is difficult to popularize and apply it in a short time. In the existing NdFeB preparation method, a low B component (0.8-0.93wt.%) is used to melt the alloy to form a certain 6:13:1 phase to prepare a sintered magnet, and the magnet is heat-treated in the temperature range of 400-600 degrees Celsius for 10 seconds to less than 30 minutes to obtain a sintered magnet with high remanence and high coercivity. However, the aging temperature range of this type of magnet is very narrow. For R-Fe-B magnets with different Cu-Ga contents, the aging temperature range is only 10-20 degrees Celsius, which increases the difficulty of exploring the optimal temperature range during the production process, resulting in a low increase in the actual coercivity of this type of magnet. Secondly, the low B and high Cu-Ga sintered NdFeB magnets generate a large amount of 6:13:1 grain boundary phases, which inevitably leads to a decrease in the volume fraction of the main phase and a decrease in remanence. The 6:13:1 grain boundary phase has poor stability, and the squareness of the magnet is greatly affected by the process conditions, resulting in the squareness of this type of magnet being less than 95%, which directly leads to poor high-temperature magnetic properties of the magnet. Finally, since a large amount of rare earth-rich phases will precipitate in the grain boundary phases in the low B and high Cu-Ga sintered NdFeB magnets, the saturated vapor pressure of rare earth elements is very low. Therefore, during the high vacuum aging process, the rare earth-rich phases will volatilize in large quantities, resulting in a decrease in the rare earth content in the grain boundary phases, and then the demagnetization coupling effect between adjacent grains decreases, and finally the coercive force of the magnet decreases.
[0005] Therefore, how to broaden the aging temperature zone of low B and high Cu-Ga sintered NdFeB magnets, inhibit the volatilization of rare earth-rich phase, optimize the magnet microstructure, improve the stability of 6:13:1 grain boundary phase, and further improve the coercive force and squareness of the magnet are technical problems that need to be solved urgently. Summary of the invention
[0006] The purpose of the present invention is to make up for the above-mentioned deficiencies and disclose to the public a preparation method for improving the coercive force and squareness of NdFeB magnets. The method adopts aging in an inert atmosphere to promote heat conduction in the furnace and adjust the saturated vapor pressure of rare earth in the furnace, which can promote the formation of a large number of stable 6:13:1 grain boundary phases and significantly improve the coercive force and squareness of the magnet.
[0007] The technical solution of the present invention is achieved in this way: A preparation method for improving the coercivity and squareness of a NdFeB magnet comprises the following steps: Step 1, ingredients: B content is 0.8-0.93 wt.%, R rare earth content is 28-35 wt.%, Cu and Ga total content is 0.01-1.0 wt.%, Co, Al, Zr, Ti, Nb total content is 0.01-5.0 wt.%, and the rest is Fe; Step 2: Rapid solidification and strip throwing: using a rapid solidification and strip throwing furnace to obtain NdFeB strip throwing sheets; Step 3, hydrogen crushing: hydrogen crushing the NdFeB strips to obtain coarse powder after hydrogen crushing; Step 4, air flow milling: grinding the hydrogen crushed coarse powder in an air flow mill to obtain magnetic powder; Step 5: Pressing and isostatic pressing: Orienting and isostatically pressing the magnetic powder to obtain a NdFeB compact; Step 6: Sintering: Control the vacuum degree to 5*10 -3 Pa, sintering at a high temperature of 950-1100℃ for 2-10 hours to obtain a sintered NdFeB magnet; performing aging heat treatment, the aging heat treatment process includes: a primary aging temperature of 850-950 degrees Celsius, keeping warm for 2-5 hours, a secondary aging temperature of 400-600 degrees Celsius, an inert gas atmosphere aging, a pressure of 0.01-0.08MPa, keeping warm for 0.5-10 hours, after the aging heat treatment is completed, the inert gas is extracted and then filled with nitrogen to cool to room temperature to obtain a NdFeB magnet.
[0008] Preferably, in the step 2, the smelting temperature is controlled at 1350-1450°C.
[0009] Preferably, in the step three, the particle size of the hydrogen-crushed coarse powder is 100-500 μm.
[0010] Preferably, in step 4, the particle size of the magnetic powder obtained by jet milling is 2-3 μm.
[0011] Preferably, in step 6, during the aging heat treatment, the vacuum is first evacuated to 1*10 -2 Pa, and then introduce 0.01-0.08MPa inert gas.
[0012] Preferably, the inert gas is argon or helium.
[0013] The advantages of the present invention compared with the prior art are: For NdFeB magnets with low B and high Cu-Ga in a narrow aging temperature range, aging is carried out in an inert atmosphere to promote heat conduction in the furnace, adjust the rare earth saturated vapor pressure in the furnace, reduce the large-scale volatilization of rare earth elements, and thus optimize the magnet microstructure, promote the formation of a large number of stable 6:13:1 grain boundary phases, and significantly improve the coercive force and squareness of the magnet.
[0014] In addition, the preparation method can broaden the aging temperature range of the magnet, so that the coercive force and squareness of this type of NdFeB sintered magnet can be optimized in a conventional two-step aging process, thereby reducing industrial production costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 11 is a comparison diagram of magnetic properties of D10×10M sample columns of Example 3 of the present invention and Comparative Example 1; Figure 2 This is a microstructure diagram of the magnet of Example 3 of the present invention; Figure 3 It is the microstructure diagram of comparative example 1; Figure 4 It is a transmission electron microscope comparison diagram of the grain boundary width of Example 3 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0016] The present invention is further described in detail below in conjunction with the accompanying drawings: A preparation method for improving the coercivity and squareness of a NdFeB magnet comprises the following steps: Step 1, ingredients: B content is 0.8-0.93 wt.%, R rare earth content is 28-35 wt.%, Cu and Ga total content is 0.01-1.0 wt.%, Co, Al, Zr, Ti, Nb total content is 0.01-5.0 wt.%, and the rest is Fe; Step 2: Rapid solidification and strip throwing: using a rapid solidification and strip throwing furnace, the melting temperature is controlled at 1350-1450°C to obtain NdFeB strip throwing sheets; Step 3, hydrogen crushing: hydrogen crushing the NdFeB strip to obtain hydrogen crushed coarse powder, the particle size of the hydrogen crushed coarse powder is 100-500μm; Step 4, air flow milling: grinding the hydrogen crushed coarse powder in an air flow mill to obtain magnetic powder, the particle size of the magnetic powder obtained by the air flow milling is 2-3 μm; Step 5: Pressing and isostatic pressing: Orienting and isostatically pressing the magnetic powder to obtain a NdFeB compact; Step 6: Sintering: Control the vacuum degree to 5*10 -3 Pa, sintering at a high temperature of 950-1100℃ for 2-10 hours to obtain a sintered NdFeB magnet; performing aging heat treatment, the aging heat treatment process includes: a primary aging temperature of 850-950 degrees Celsius, keeping warm for 2-5 hours, a secondary aging temperature of 400-600 degrees Celsius, an inert gas atmosphere aging, a pressure of 0.01-0.08MPa, keeping warm for 0.5-10 hours, after the aging heat treatment is completed, the inert gas is extracted and then filled with nitrogen to cool to room temperature to obtain a NdFeB magnet.
[0017] Furthermore, during the aging heat treatment process, the vacuum is first evacuated to 1*10 -2 Pa, and then introduce 0.01-0.08MPa inert gas.
[0018] The inert gas is preferably argon or helium, which are easy to obtain and have low cost.
[0019] The following is further described by examples: Example 1 Step 1: R in weight percentage 30 Fe bal (CuGa) 0.3 B 0.90 (CoZrTiAl) 1.1 The low-boron formula is used for batching; Step 2: Rapid solidification and strip throwing: using a rapid solidification and strip throwing furnace, the melting temperature is controlled at 1350-1450°C to obtain NdFeB strip throwing sheets; Step 3, hydrogen crushing: hydrogen crushing the NdFeB strip to obtain hydrogen crushed coarse powder, the particle size of the hydrogen crushed coarse powder is 100-500μm; Step 4, air flow milling: grinding the hydrogen crushed coarse powder in an air flow mill to obtain magnetic powder, the particle size of the magnetic powder obtained by the air flow milling is 2-3 μm; Step 5: Pressing and isostatic pressing: Orienting and isostatically pressing the magnetic powder to obtain a NdFeB compact; Step 6: Sintering: Control the vacuum degree to 5*10 -3 Pa, sintering at 950-1100℃ for 2-10 hours to obtain a sintered NdFeB magnet; performing aging heat treatment, the aging heat treatment process includes: a primary aging temperature of 890℃, holding for 4 hours, a secondary aging temperature of 450℃, an inert gas atmosphere aging, and holding for 5 hours; wherein the heating process is 1h, and when the temperature is raised to 450℃, an inert gas argon is filled in, and the pressure is 0.01MPa; after the aging is completed, the argon is extracted and then filled in with nitrogen to cool to room temperature to obtain a NdFeB magnet.
[0020] The aging blanks were sampled (10-point sampling method, according to the position of the blanks in the furnace, 9 points in the three-dimensional space plus any point were sampled), and the coercivity (Hcj) and squareness (SQ) of the blank magnets were tested at room temperature (20°C). The test data of the sampled blanks are shown in Table 1: Table 1 Test results of sample blanks of Example 1
[0021] Example 2 In this embodiment, the raw material formula, preparation method and blank sampling method are the same as those in Example 1, except that during the secondary aging, 0.03 MPa of inert gas argon is introduced. The blank sampling test data is shown in Table 2: Table 2 Test results of sample blanks of Example 2
[0022] Example 3 In this embodiment, the raw material formula, preparation method and blank sampling method are the same as those in Example 1, except that during the secondary aging, 0.05 MPa of inert gas argon is introduced. The blank sampling test data is shown in Table 3: Table 3 Test results of sample blanks of Example 3
[0023] Example 4 In this embodiment, the raw material formula, preparation method and blank sampling method are the same as those in Example 1, except that during the secondary aging, 0.08 MPa of inert gas argon is introduced. The blank sampling test data is shown in Table 4: Table 4 Test results of sample blanks of Example 4
[0024] Comparative Example 1 The raw material formula, preparation method and blank sampling method are the same as those in Example 1, except that the sintered NdFeB magnets are subjected to two-stage aging, which includes: the first-stage aging temperature is 890 degrees Celsius, and the temperature is kept for 4 hours; the second-stage aging temperature is 480 degrees Celsius, and the temperature is kept for 5 hours, and the heating time is 1 hour. The aging process is in a high vacuum state, and the internal pressure is 10 -3 ~10 -4 Pa, after the aging period, nitrogen was filled in and cooled to room temperature.
[0025] The test data of the sampled blank is shown in Table 5: Table 5 Test results of sample blanks of comparative example 1
[0026] The aging process of the sampled blanks of Examples 1-4 and Comparative Example 1 and the corresponding test coercivity and squareness ranges are shown in Table 6: Table 6 Aging process of the blank samples of Examples 1-4 and Comparative Example 1 and the corresponding test coercivity and squareness range project Filling with gas Aging furnace pressure Coercivity-Hcj / kOe Squareness-SQ / % Example 1 Argon 0.01MPa 17.09-17.88 93.2-96.2 Example 2 Argon 0.03MPa 18.03-18.61 94.2-97.7 Example 3 Argon 0.05MPa 18.18-18.74 95.2-98 Example 4 Argon 0.08MPa 18.61-18.90 95.82-97.87 Comparative Example 1 High vacuum <![CDATA[10 -3 ~10 -4 Well]]> 15.73-17.56 87.7-96 Figure 1 This is a comparison diagram of the magnetic properties of the D10×10M sample column of Example 3 and Comparative Example 1. It can be seen that the magnet of Example 3 has higher coercivity and better squareness than that of Comparative Example 1. It can be seen that the magnet prepared by the preparation method of the present invention can obtain higher coercivity and squareness consistency; Figure 2 This is the magnet microstructure diagram of Example 3. Figure 3 This is a microstructure diagram of comparative example 1. It can be seen that the magnet prepared by the method of the present invention has a clear and continuous grain boundary phase, and the segregation of oxygen content in the grain boundary is significantly reduced.
[0027] Figure 43 is a transmission electron microscope comparison of the grain boundary width of Example 3 of the present invention and Comparative Example 1. Figure 4 As shown, for the comparative magnet, due to the vacuum environment, the heat conduction is low, although the NdFeB magnet can see the continuous grain boundary phase, the grain boundary width is only 2.04nm, indicating that the local demagnetization coupling effect of the magnet is poor. At the same time, the 6:13:1 grain boundary phase with gray symmetry in the boundary can also be seen, but the grain size is very uneven, and the uneven grain size causes the magnet coercive force and squareness to be poor. For the magnet of Example 3, there is not only a continuous grain boundary in the magnet, but also a gray symmetry in the continuous grain boundary, indicating that a continuous grain boundary phase is formed, and the grain boundary phase width is about 14.2nm, which is far more than the exchange coupling length of 2.1nm, indicating that it is conducive to improving the demagnetization coupling effect of the magnet grain boundary phase under an inert gas environment and improving the magnet coercive force. At the same time, due to the inert gas for heat conduction, the magnet grain size is slightly grown, but the grain size is relatively uniform, and the continuous grain boundary and uniform grains are conducive to the improvement of the magnet coercive force and squareness.
[0028] Example 5 Step 1: R in weight percentage 31.8 Fe bal (CuGa) 0.8 B 0.85 (CoZrTiAl) 1.0 The low-boron formula is used for batching; Step 2: Rapid solidification and strip throwing: using a rapid solidification and strip throwing furnace, the melting temperature is controlled at 1350-1450°C to obtain NdFeB strip throwing sheets; Step 3, hydrogen crushing: hydrogen crushing the NdFeB strip to obtain hydrogen crushed coarse powder, the particle size of the hydrogen crushed coarse powder is 100-500μm; Step 4, air flow milling: grinding the hydrogen crushed coarse powder in an air flow mill to obtain magnetic powder, the particle size of the magnetic powder obtained by the air flow milling is 2-3 μm; Step 5: Pressing and isostatic pressing: Orienting and isostatically pressing the magnetic powder to obtain a NdFeB compact; Step 6: Sintering: Control the vacuum degree to 5*10 -3 Pa, sinter at 950-1100℃ for 2-10 hours to obtain a sintered NdFeB magnet; perform aging heat treatment, the aging heat treatment process includes: primary aging temperature is 890℃, insulation for 4 hours, secondary aging temperature is 450℃, atmosphere aging uses inert gas, insulation for 5 hours; during the heating process of 1h, when the temperature rises to 430℃, inert gas helium is filled in, and the injection pressure is 0.03MPa; after the aging is completed, the helium is extracted and then filled in with nitrogen to cool to room temperature to obtain a NdFeB magnet.
[0029] The aging blanks were sampled (10-point sampling method, according to the position of the blanks in the furnace, 9 points in the three-dimensional space plus any point were sampled), and the coercivity (Hcj) and squareness (SQ) of the blank magnets were tested at room temperature (20°C). The test data of the sampled blanks are shown in Table 7: Table 7 Test results of sample blanks of Example 5
[0030] Example 6 In this embodiment, the raw material formula, preparation method and blank sampling method are the same as those in Example 5, except that during the secondary aging, 0.05MPa of inert gas helium is introduced. The blank sampling test data is shown in Table 8: Table 8 Test results of sample blanks from Example 6
[0031] Example 7 In this embodiment, the raw material formula, preparation method and blank sampling method are the same as those in Example 5, except that during the secondary aging, 0.08 MPa of inert gas helium is introduced. The blank sampling test data is shown in Table 9: Table 9 Test results of sample blanks of Example 7
[0032] Comparative Example 2 The raw material formula, preparation method and blank sampling method are the same as those in Example 5, except that the sintered NdFeB magnets are subjected to two-stage aging, which includes: the first-stage aging temperature is 890 degrees Celsius, and the temperature is kept for 4 hours; the second-stage aging temperature is 450 degrees Celsius, and the temperature is kept for 6 hours, and the heating time is 1 hour. The aging process is in a high vacuum state, and the internal pressure is 10 -3 ~10 -4 Pa, after the aging period, nitrogen was filled in and cooled to room temperature.
[0033] The test data of the sampled blank is shown in Table 10: Table 10 Comparative Example 2 Sampling Blank Test Results
[0034] The aging process of the sampled blanks of Examples 5-7 and Comparative Example 2 and the corresponding test coercivity and squareness ranges are shown in Table 11 below: Table 11 Aging process of the blank samples of Examples 5-7 and Comparative Example 2 and the corresponding test coercivity and squareness range project Filling with gas Aging furnace pressure Coercivity-Hcj / kOe Squareness-SQ / % Example 5 Helium 0.03MPa 20.08-20.28 94.7-96.5 Example 6 Helium 0.05MPa 20.26-20.61 97.1-97.8 Example 7 Helium 0.08MPa 20.52-20.72 97.4-97.9 Comparative Example 2 High vacuum <![CDATA[10 -3 ~10 -4 Well]]> 18.95-20.27 88.4-95 From the test data of the above embodiments and comparative examples, the coercivity of the magnet prepared by the preparation method of the present invention is increased by 0.3-1kOe, and the consistency of coercivity and squareness is significantly improved. It is worth noting that during aging, when the furnace atmosphere uses inert gas argon or helium, and the pressure increases from 0.05MPa to 0.08MPa, the improvement of squareness is not obvious but is above 95%, and the increase of coercivity slows down. The actual production process can comprehensively evaluate the production performance requirements and production costs, so as to select the appropriate pressure.
[0035] The aging process of the conventional preparation process of NdFeB magnets is completed in a vacuum environment. Since the rare earth elements will be pumped away by a vacuum pump after volatilization, the saturated vapor pressure of the rare earth elements in the vacuum environment is relatively low, and the heat conduction in the vacuum environment is very low. The present invention adopts inert gases with different air pressures (0.01-0.08MPa) to increase the heat conduction process during high-temperature aging, and the volatilized rare earth elements are enriched in the sintering furnace, which inhibits the further volatilization of the rare earth elements in the magnet, reduces the loss of rare earth elements, and is conducive to ensuring the total amount of rare earth in the final magnet. More importantly, aging heat treatment is carried out in an environment with inert gas to improve the heat conduction effect, stabilize the 6:13:1 grain boundary phase in the low B high Cu-Ga magnet, and can improve the coercive force and squareness of the magnet.
[0036] The best embodiment of the present invention has been described, and various changes or modifications may be made by those skilled in the art without departing from the scope of the present invention.
Claims
1. A method for preparing a NdFeB magnet with improved coercivity and squareness, characterized in that: The following steps are involved: Step 1, ingredients: B content is 0.8-0.93 wt.%, R rare earth content is 28-35 wt.%, Cu and Ga total content is 0.01-1.0 wt.%, Co, Al, Zr, Ti, Nb total content is 0.01-5.0 wt.%, and the rest is Fe; Step 2: Rapid solidification and strip throwing: using a rapid solidification and strip throwing furnace to obtain NdFeB strip throwing sheets; Step 3, hydrogen crushing: hydrogen crushing the NdFeB strips to obtain coarse powder after hydrogen crushing; Step 4, air flow milling: grinding the hydrogen crushed coarse powder in an air flow mill to obtain magnetic powder; Step 5: Pressing and isostatic pressing: Orienting and isostatically pressing the magnetic powder to obtain a NdFeB compact; Step 6: Sintering: Control the vacuum degree to 5*10 -3 Pa, sintering at a high temperature of 950-1100℃ for 2-10 hours to obtain a sintered NdFeB magnet; performing aging heat treatment, the aging heat treatment process includes: a primary aging temperature of 850-950 degrees Celsius, keeping warm for 2-5 hours, a secondary aging temperature of 400-600 degrees Celsius, an inert gas atmosphere aging, a pressure of 0.01-0.08MPa, keeping warm for 0.5-10 hours, after the aging heat treatment is completed, the inert gas is extracted and then filled with nitrogen to cool to room temperature to obtain a NdFeB magnet.
2. A method for preparing a NdFeB magnet for improving coercivity and squareness according to claim 1, characterized in that: In the step 2, the smelting temperature is controlled at 1350-1450°C.
3. The method for preparing a NdFeB magnet for improving coercivity and squareness according to claim 1, characterized in that: In the step 3, the particle size of the hydrogen-crushed coarse powder is 100-500 μm.
4. The method for preparing a NdFeB magnet for improving coercivity and squareness according to claim 1, characterized in that: In the step 4, the particle size of the magnetic powder obtained by the jet mill is 2-3 μm.
5. The method for preparing a NdFeB magnet for improving coercivity and squareness according to claim 1, characterized in that: In step 6, during the aging heat treatment, the vacuum is first evacuated to 1*10 -2 Pa, and then introduce 0.01-0.08MPa inert gas.
6. The method for preparing a NdFeB magnet for improving coercivity and squareness according to claim 1, characterized in that: The inert gas is argon or helium.
Citation Information
Patent Citations
Method for preparing high-magnetic energy product high-coercive force low-cost sintered neodymium iron boron
CN102031445A
Preparation process of a sintered NdFeB permanent magnet
CN107658088A
Preparation method of sintered neodymium-iron-boron magnet with high magnetic energy product and high coercive force
CN108565086A
Preparation method of low-heavy-rare-earth high-coercivity neodymium-iron-boron permanent magnet material
CN116313491A
Low-boron high-coercivity neodymium iron boron permanent magnet
CN119108173A